Gender Lessons - Richardson, Scott. author. aut Link
XX, 220 p.
Keywords: Public schools in early America were designed to ensure the reproduction of Eurocentric social values. It could be argued that little has changed. Gender Lessons takes an in-depth look at how schools institutionalize gender—how kids are taught the rules and expectations of performing masculinity and femininity. This work provides extensive examples of how elementary, middle, and high schools: sextype; defend and preserve patriarchy; weave gendered expectations in all things school related; promote inequity; and limit their students’ potential by explicitly and implicitly teaching that they must fit into only one of two boxes…“girl” or “boy.” Richardson argues that schools—a powerful and wide reaching publicly funded mechanism—should be engaged in social (re)imagination that disbands the antiquated girl/boy and feminine/masculine binary so that kids might have a chance at being themselves. This book is sure to provoke conversation in courses and professional communities interested in education, gender studies, social work, sociology, counseling and guidance. “In the 1970s, feminists fought to reform sexist school curricula and challenged taken-for-granted tracking of boys and girls. Forty years later, drawing from personal experiences and insightful research in schools, Scott Richardson shows us that the job is far from finished. Informal interactions and stubborn sexist beliefs about gender difference still press girls and boys in primary, middle and high schools into different—and highly constraining—gender boxes. Anyone who cares about taking the next steps toward gender equality in schools will find in Gender Lessons a useful and hopeful map to a better future for our kids.” – Michael A. Messner, Ph.D., Professor of Sociology and Gender Studies at the University of California, Berkeley and author of Some Men: Feminist Allies and the Movement to End Violence Against Women “This book is unique in that it includes data from elementary,middle, and high schools from both students’ and teachers’ perspectives. These examples are familiar to anyone working in K-12 schools, but his analysis offers a new lens for many that can expose the frustrating and often heartbreaking nature of these taken-for-granted cultural norms.” – Elizabeth J. Meyer, Ph.D., Assistant Professor of Education at California Polytechnic State University and author of Gender and Sexual Diversity in Schools.